2015
DOI: 10.1037/a0037674
|View full text |Cite
|
Sign up to set email alerts
|

How “situational” is judgment in situational judgment tests?

Abstract: Whereas situational judgment tests (SJTs) have traditionally been conceptualized as low-fidelity simulations with an emphasis on contextualized situation descriptions and context-dependent knowledge, a recent perspective views SJTs as measures of more general domain (context-independent) knowledge. In the current research, we contrasted these 2 perspectives in 3 studies by removing the situation descriptions (i.e., item stems) from SJTs. Across studies, the traditional contextualized SJT perspective was not su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
172
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 77 publications
(192 citation statements)
references
References 59 publications
16
172
0
2
Order By: Relevance
“…Furthermore, the evidence provided by Krumm et al (2015) does not rule out this suggestion. Even though Krumm et al (2015) write that "use of general knowledge" was related to a higher likelihood of choosing the correct response option (p. 410), many of the examples in their article suggest to us that this knowledge was related to the correct interpretation of the situation in the first step.…”
Section: Why Does Situational Judgment Matter Even Without a Descriptmentioning
confidence: 91%
“…Furthermore, the evidence provided by Krumm et al (2015) does not rule out this suggestion. Even though Krumm et al (2015) write that "use of general knowledge" was related to a higher likelihood of choosing the correct response option (p. 410), many of the examples in their article suggest to us that this knowledge was related to the correct interpretation of the situation in the first step.…”
Section: Why Does Situational Judgment Matter Even Without a Descriptmentioning
confidence: 91%
“…Consistency in SJT performance for versions with and without prompts (Krumm et al, 2015) might reflect the previously noted issue that situational cues are still present and clear in the response options of SJTs, such that the two versions do not reflect a substantial difference in situational strength (i.e., general domain knowledge is important in both measures). This interpretation of the role of situational strength is consistent with Rockstuhl et al's (2015) finding that SJTs that explicitly ask respondents to judge the situation provide incremental validity over SJTs that do not, as well as consistent with studies showing the importance of situational cues in other assessment formats (Jansen et al, 2013;Melchers et al, 2012).…”
Section: The Role Of Situational Strengthmentioning
confidence: 97%
“…So, this study showed that situational judgment could capture important predictive information. The problem, however, is that it is not measured in traditional multiple-choice SJTs, which echoes the conclusions of Krumm et al (2015).…”
Section: Recent Empirical Research Evidencementioning
confidence: 98%